2021
DOI: 10.3390/cancers13215373
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin 5 (TSPAN5), a Novel Gatekeeper of the Tumor Suppressor DLC1 and Myocardin-Related Transcription Factors (MRTFs), Controls HCC Growth and Senescence

Abstract: Human hepatocellular carcinoma (HCC) is among the most lethal and common cancers in the human population, and new molecular targets for therapeutic intervention are urgently needed. Deleted in liver cancer 1 (DLC1) was originally identified as a tumor suppressor gene in human HCC. DLC1 is a Rho-GTPase-activating protein (RhoGAP) which accelerates the return of RhoGTPases to an inactive state. We recently described that the restoration of DLC1 expression induces cellular senescence. However, this principle is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Tetraspanin 5 (TSPAN5) is strongly up-regulated in DLC1-deficient HCC cells, while silencing TSPAN5 induces oncogene-induced senescence mediated by the p16/pRb pathways. 45 Depletion of the transcriptional coactivators MLK1/2 eliminates DLC1-deficient HCC xenograft growth, but reconstitution of DLC1 in HuH7 HCC cells induces cell senescence. 14 Our previous results have shown that DLC1 promotes cell senescence through the FoxO3a/NF-κB signaling pathway or endoplasmic reticulum stress after resveratrol treatment in lung and breast cancer cells.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Tetraspanin 5 (TSPAN5) is strongly up-regulated in DLC1-deficient HCC cells, while silencing TSPAN5 induces oncogene-induced senescence mediated by the p16/pRb pathways. 45 Depletion of the transcriptional coactivators MLK1/2 eliminates DLC1-deficient HCC xenograft growth, but reconstitution of DLC1 in HuH7 HCC cells induces cell senescence. 14 Our previous results have shown that DLC1 promotes cell senescence through the FoxO3a/NF-κB signaling pathway or endoplasmic reticulum stress after resveratrol treatment in lung and breast cancer cells.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Our previous studies demonstrated that pharmacological blockade or depletion of MRTFs or their target genes Myoferlin or Tetraspanin 5 inhibits HCC growth by inducing oncogene-induced senescence [ 3 , 8 , 10 , 11 ]. We therefore searched for novel druggable targets at the plasma membrane overexpressed in human HCC patient samples that could constitute novel therapeutic targets to prevent MRTF function and HCC growth.…”
Section: Resultsmentioning
confidence: 99%
“…Since senescence induction functions as a tumor-suppressive mechanism, strategies aimed at the induction of cellular senescence have gained considerable attention for HCC therapy [ 3 ]. We recently implicated MRTFs and their target genes Myoferlin and Tetraspanin 5 in the senescence response [ 10 , 11 ], but the mechanisms driving the MRTF-associated senescence response remain unclear. Here, we show that LPAR1 activation facilitates FLNA phosphorylation at S2152, complex formation with MRTF-A, stress fiber- and focal adhesion formation, whereas impairment of FLNA phosphorylation caused by LPAR1 depletion or blockade redistributes MRTF-A to the cytoplasm and drives HCC cells into senescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSPAN5 has a regulatory effect on the transport of ADAM10 from vesicles to the protoplasmic reticulum, and regulatory disturbances in these interactions may be associated with disorders that cause cancer, Alzheimer’s disease, or inflammation [ 18 , 19 ]. In cancerous tumors, TSPAN5 plays a role in hepatocellular carcinoma (HCC) metastasis through epithelial-mesenchymal transition [ 20 ] and regulates the growth of HCC in co-operation with other genes [ 21 ]. However, its role in colorectal cancer has not been clearly identified.…”
Section: Introductionmentioning
confidence: 99%